Frequency of Cervical, Thoracic and Lumber Pain and Postural Changes in Madrassa Students: Cervical, Thoracic, Lumber Pain and Postural Changes in Students - Masood, Ramsha; Razi, Fatima; Zafar, Ibraheem; Shafiq, Muhammad Saad; Ahmad, Naveed; Naz, Iqra; Aslam, Memoona (Pakistan BioMedical Journal, 2022)
Musculoskeletal pain and abnormal postural change is very common among school going students. The prevalence is also high in madrassa students. Their number increase because of bad posture, prolong sitting and repetitive movement. Objective: The objective of the study was to find the frequency of pain in cervical, thoracic, and lumbar spine and postural abnormalities occurring in madrassa students. Methods: This is a descriptive cross sectional study which was conducted from 15th February 2016 to 28th June 2016 at different madrassa’s of Rawalpindi and Islamabad. This include: Madrassa Zia-ul-Quran, Shah Khalid Colony Rawalpindi, DarulSufah Faisal Colony Rawalpindi, Madrassa Hazrat Abdullah bin Abbas(R.A) Islamabad, Madrassa Hazrat Salman Pharsi(R.A) DhokMangtal, Rawalpindi, Madrassa Abdullah bin Umar (R.A) Jinnah Garden, Phase I, Islamabad, Madrassa KhadijahtulQubra, Khayaban-e-Sirsyed, Rawalpindi, JamyaAmna Zia ulBinat, Railway scheme 7, Rawalpindi. A sample of 205 male and female madrassa students (age 10-17year) was recruited through convenient sampling. The inclusion criteria was both gender, male & female, Age; 10-17, only madrassa students, exclusion criteria was, students above the age of 17 years, students under 10 year of age, children with poliomyelitis, active tuberculosis, neurological problems, congenital deformities Normal posture and pain was assessed by Adam’s bend test and Numeric pain rating scale (NRPS). Later the data was analyzed through SPSS 17. Result: A total sample size of 205 was selected in which 61% were male students and 39% were female students. The mean age of the madrassa students is 13.19±2.06 of which 12.98±2.00 male and 13.51±2.14.Out of 205(100%) madrassa students 74.6% madrassa students have pain, most of them have moderate intensity of pain 55.6% and 12.7% have severe intensity of pain and 25.4% madrassa students have no pain. 78.5% of the madrassa students were sitting with low level of desk and 21.5% with appropriate leveled height of the desk. Only 6.8% of madrassa students have activity restriction due to pain. Forward head posture is present in 37.1% of madrassa students and absent in 62.9% of the students out of 100%. 36.6% of madrassa students presents with rounded shoulders. Out of 100% of madrassa students 36.1% of madrassa students have increased thoracic kyphotic and lumber Lordotic curve.In 11.7% of the madrassa students Adams forward bending test for scoliosis came positive and negative in 88.3% of the madrassa students. Conclusion: It is concluded that the cervical and lumber pain is more prevalent in madrassa students and some of the students show increased kyphotic and lordotic curves which is correlated with long periods of sitting for recitation in forward flexion of head, neck, and back and poor posture maintenance.